Aplikasi Akad Tabarru’ Wadi’ah dan Qard di Perbankan Syariah - Ilda Hayati (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The economic transaction in Islam is not always to orientate on commercial, and profit-oriented activity. It is namely with tabbaru‟—all of agreement intentionally related to non-profit. The „aqd can be an activity of which gives or borrows something. In fact, especially in Islamic Bank, that „aqd is consistently maintained in the tabbaru‟ principles. The existed-cost in conserving, is obviously as an avoindance-compentation. The paper will examine the wadi‟ah concept and qard in Islamic Bank. Keywords: Application, Tabbaru‟ „Aqd, Wadiah, Qard and Islamic Bank.